The role of transarterial chemoembolization with drug-eluting beads “Sphere-Spectrum” in the treatment of primary and recurrent tumors of the female reproductive system complicated by bleeding - E. A. Zvezdkina; A. G. Kedrova; D. P. Lebedev; T. A. Greyan; D. N. Panchenkov; Yu. A. Stepanova; S. E. Krasilnikov; K. S. Budennyy (Опухоли женской репродуктивной системы)
Background. Transarterial chemoembolization (TACE) with drug-eluting beads has been used in the treatment of tumors of the female reproductive system complicated by bleeding. However, questions arise: how to integrate the method into the treatment regimen and at what stage should it be applied?Aim. To evaluate the effectiveness of TACE in tumors of the female reproductive system complicated by bleeding at different stages of the disease.Materials and methods. A retrospective analysis of 80 women with primary (group 1) and 20 with recurrent tumors (group 2) of the reproductive system, who underwent 110 TACE with drug-eluting beads “Sphere-Spectrum” (100 primary, 10 repeated), is presented. Mostly used drug-eluting beads “Sphere-Spectrum”. The indication for TACE was tumor bleeding. For dynamic control, magnetic resonance imaging of the small pelvis was performed no later than 14 days before, 14–21 days and 1–3 months after TACE.Results. Hemostasis after TACE in all cases was achieved by the end of 1 day. There was no progression of the tumor process in any case. In group 1, 56 women (70 %) after TACE were operated on (stages 1B–2A), although according to preoperative magnetic resonance imaging staging, only 34 women (43 %) were subject to surgical treatment; 3 women underwent radiation therapy, 23 – chemoradiotherapy, systemic chemotherapy and immunotherapy in accordance with the stage of the disease. In group 2, 3 women were operated on after correction of their somatic condition and tumor reduction, 3 women underwent chemoradiotherapy, 14 women continued systemic chemotherapy.Conclusion. TACE has shown high efficiency as a hemostatic and antitumor therapy. It should be included in the treatment regimen for women with bleeding from tumors of the reproductive system at any stage of the disease, which allows expanding the available options for antitumor therapy for this category of patients; at the same time, the use of TACE as a monomethod requires further study.